2023
DOI: 10.3233/wor-210467
|View full text |Cite
|
Sign up to set email alerts
|

Labor of love, or love of labor? Psychological capital’s mitigating role in the relationship between workaholism and work stress

Abstract: BACKGROUND: Workaholism is conceptualized as a compulsive need to work incessantly, and it is related to numerous detrimental organizational and individual consequences. For that reason, it is imperative that researchers uncover possible variables that can alleviate its potentially harmful effects. OBJECTIVE: This study aims to examine the relationship between workaholism, psychological capital (PsyCap), physical health, and work stress. The potential mitigating role that PsyCap could play between workaholism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…9 Previous research has demonstrated that psychological capital has preventive and promotive effects on physical and mental health, as well as subjective well-being in college students 10 or employees. 11 A positive psychological state improves an individual's perception of negative experiences and fosters a sense of self-worth, leading to a positive outlook on illness and daily life. Post-traumatic growth (PTG) refers to the positive psychological changes experienced by individuals while navigating through traumatic events.…”
Section: Introductionmentioning
confidence: 99%
“…9 Previous research has demonstrated that psychological capital has preventive and promotive effects on physical and mental health, as well as subjective well-being in college students 10 or employees. 11 A positive psychological state improves an individual's perception of negative experiences and fosters a sense of self-worth, leading to a positive outlook on illness and daily life. Post-traumatic growth (PTG) refers to the positive psychological changes experienced by individuals while navigating through traumatic events.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that individuals with higher psychological capital have higher job satisfaction, better job performance, less work stress, and lower turnover intention [22][23] . Previous research has examined the association between psychological capital and work stress in the general population [24][25][26] . The results showed that individuals with high levels of psychological capital tended to report lower levels of work stress 24,26 .…”
Section: Introductionmentioning
confidence: 99%